Construction of Reporting on the 2024 Female Presidential Candidates on Tirto.id, Tempo.co, and Kompas.com - Dudi Iskandar; Indah Suryawati; Liliyana Liliyana (Nyimak: Journal of Communication, 2022)
In the middle of a patriarchal culture, several females pushed the competition map for the 2024 presidential candidate which was dominated by males. However, the votes were insignificant and only a few names appeared in the survey results. Apart from the 30% affirmative action, the role of the media in promoting gender mainstreaming in politics is needed because news about female presidential candidates is still relatively rare. Therefore, this research aims to reveal the news of the 2024 female presidential candidate survey results presented by tirto. id, tempo.co, and kompas.com. This was conducted using the framing analysis method of the Robert Matthew Entman model consisting of two dimensions, namely issue selection, and aspect highlight, as well as four framing elements, including problem definition, sources, moral decisions, and problem-solving. The result showed several interesting points. First, all the media analyzed presented news about females’ inability and resources based on the results of various surveys. Second, all news presented an interpretive journalism model that reads and interprets survey data by experts. Third, although they try to deny the patriarchal ideology, the majority present male commentators who review female political communication. This means that ideology still surrounds the three online media studied.Keywords: Female presidential candidates, news, online media, framing analysis ABSTRAKDi tengah kultur patriarkhi, beberapa perempuan menyeruak peta persaingan capres 2004 yang didominasi capres laki-laki. Meski begitu suaranya tidak signifikan, hanya beberapa nama saja yang muncul dihasil survei. Selain affirmative action 30 persen, peran media mendorong pengarusutamaan gender di bidang politik sangat dibutuhkan. Saat ini pemberitaan tentang capres perempuan relatif jarang. Padahal melalui pemberitaan yang masif dan kontinyu, capres perempuan akan diperhitungkan. Di tengah capres perempuan yang jarang diberitakan, penelitian ini menemukan signifikansinya. Bahwa capres perempuan jarang diberitakan dibandingkan capres laki-laki. Penelitianbertujuan menguak berita hasil survei capres perempuan 2024 yang disajikan tirto.id, tempo.co, dan kompas.com. Penelitian ini menggunakan metode analisis framing model Robert Matthew Entman yang memiliki dua dimensi (seleksi isu dan penonjolan aspek) serta empat elemen framing (Pendefinisain masalah, sumber masalah, keputusan moral, dan penyelesaian masalah). Sebagai kesimpulan, penelitian ini menemukan beberapa poin menarik. Pertama, semua media yang diteliti menyajikan berita tentang kekurangmampuan dan sumber daya perempuan yang minim berbasis hasil berbagai survei. Kedua, semua berita menyajikan model jurnalisme interpretatif yang membaca dan menafsirkan data hasil survei oleh para ahlinya. Ketiga, meski mencoba menyangkal ideologi patriarkhi, tetapi mayoritas berita menyajikan komentator laki-laki yang mengulas komunikasi politik perempuan. Artinya, ideologi patriarkhi masih menyelimuti ketiga media online yang diteliti.Kata Kunci: Capres perempuan, berita, media online, analisis framing